Strategi Konstruksi Sosial dalam Desain Kebijakan (Dampak Tradisi Belis Di Sumba) - Bewa Dangu Wole; Soleman Renda Bili (Varied Knowledge Journal, 2026)
This research aims to develop a comprehensive understanding of Social Construction Strategies in Policy Design (The Impact of the Belis Tradition in Sumba). The type of descriptive qualitative research and data analysis uses the social construction theory of Berger and Luckman, namely the three indicators of externalization, objectivity, and internalization, and the policy design offered is to form customary institutions as a special strategy to unite kabisu (tribes). The results of the research were obtained that youth traditional actors, rato rumata, and the government tourism office support the existence of customary institutions to answer the challenge of changing the meaning and cultural values of Sumba marriage that have long been held by the Loli people can be eroded or forgotten due to the search for other alternatives that are more modern and adaptive. The design of the structure of customary institutions is by forming the management of institutions such as chairmen, secretaries, and advisors at the village and sub-district levels and at the sub-district level, the Loli Customary Council abbreviated as DAL is formed. Every three months DAL holds a general meeting in the form of evaluation of work programs from each village and sub-district level institution.